Identification of antagonistic activity against Fusarium, and liquid fermentation of biocontrol Bacillus isolated from wolfberry (Lycium barbarum) rhizosphere soil - Xi, Na; Liu, Teng-Da; Zhang, Yu-Zhou; Liu, Kuo; Du, Hua-Ying; Gu, Pei-Wen; Yu, Ze-Yang; Song, Yu-Yang (Frontiers in Microbiology, 2025)
IntroductionFusarium is a kind of plant pathogenic fungus that is widely present in the soil. It can trigger a variety of plant diseases, such as wilt and root rot, which pose a serious threat to agricultural production.MethodsIn this study, a strain of Bacillus subtilis was identified by morphology, physiology, biochemistry, and molecular biology and was named LK−1.ResultsThe antagonistic curve showed that the best antagonistic fermentation time was 48 h. The fermentation broth and bacterial suspension of LK−1 had sound antagonistic effects on the mycelium or spores of F. oxysporum; when the mycelium or spores of F. oxysporum were treated with LK−1, they grew abnormally. Compared to fermentation broth, the antagonistic effect of sterile filtrate was lower. In addition, compared to the Lycium barbarum seedlings in the control group, the plant height, root length, aboveground fresh weight, underground fresh weight, aboveground dry weight, underground dry weight, and leaf area indexes of L. barbarum seedlings treated with LK−1 fermentation broth (1 × 108 cfu/mL) were all significantly higher. Using the one-way test, Plackett–Burman test, and Box–Behnken test, the fermentation medium and conditions for strain LK−1 were ultimately determined to be 0.5% glucose, 2% beef extract, 2% NaCl, and 0.5% yeast powder, with a fermentation time of 46 h, an inoculum size of 1%, a pH of 6.6, and a rotational speed of 170 rpm. Validation experiments showed that the bacterial inhibition rate under these conditions reached 62.5%, which was 1.43% higher than the theoretical value and 8.06% higher than the unoptimized value (54.44%).DiscussionLK-1 had sound preventive and control effects against many kinds of Fusarium.